(untitled) (UUM Journal of Legal Studies, 2024)
The purpose of this study is to discuss the suitability of small claim courts to solve bad credit claims that are filed by banks as an alternative to dispute contract defaults. The study analyses the trend of banks’ small claims during the COVID-19 pandemic. This study employed an empirical normative approach. It combines a normative legal approach and additional empirical elements in the form of cases and decisions. The results show that some of the regulations that were released before the pandemic, such as the Regulation of the Supreme Court Number 4 of 2019 on the Settlement of Small Claim Courts, provide benefits for banks to settle credit disputes because they allow various expansions. The Regulation of the Supreme Court Number 3 of 2018 on The Administration of Cases in Electronic Courts has introduced some electronic applications. Although business (bank) litigation remains dominant, the trend of bank claims in the middle of the COVID-19 pandemic has dropped. In contrast, the trend of individual claims has increased significantly. The decline is influenced by countercyclical policies that are issued by the Financial System Stability Committee. The committee members consist of representatives of the Ministry of Finance, Bank Indonesia, the Financial Services Authority, and the Deposit Insurance Corporation. It aims to handle and cope with the banks’ crisis related to the pandemic.